A "Cognition and Practice" Approach to an Aspect of European Kinship. (July 2017) - Heady, Patrick
Despite the long history of kinship studies, we still lack agreed theories capable of explaining the connection between terminological systems and kinship practice. This article argues for a cognitive approach centering on two distinct but complementary aspects of identity. It is argued that patterns of shared identity are implied by terminology and combine with other factors to motivate practice—in a feedback loop which transmits influences between terminological systems and political and economic institutions. The argument is illustrated by statistical and historical analyses of an aspect of European kinship.